PENGARUH RESPONSIVENESS DAN TANGIBLE TERHADAP CUSTOMER SATISFACTION PADA HOTEL LOVINA BEACH CLUB & RESORT - Ketut Priska Setialina Dewi; Putra, Komang Endrawan Sumadi (Universitas Pendidikan Ganesha, 2025)
This study aims to examine the effect of responsiveness and tangibles on customer satisfaction among guests at Lovina Beach Club & Resort Hotel. This study is intended to offer a new perspective for hotel managers to retain their customers. The population of this study is guests of Lovina Beach Club & Resort Hotel. The sampling technique used is simple random sampling. This study used a questionnaire from 100 guests staying at the Lovina Beach Club & Resort Hotel. Multiple linear regression analysis was used to analyze the collected data with the help of SPSS software version 25. The results of the study indicate that responsiveness and tangibles have a significant effect on customer satisfaction. Responsiveness has a positive and significant effect on customer satisfaction. Tangible has a positive and significant effect on customer satisfaction. The results of this study provide hotel management with an understanding of the importance of maintaining responsiveness and tangibles to improve customer satisfaction at their hotel.